LA ADMINISTRACIÓN FRENTE A LA VELOCIDAD DEL CAMBIO (2016)
Some important authors such as exponents of theories and administrative proposals made on organizations in relation to the changes have been reviewed in this article. There have been chosen some factors that the authors believe are the most influential to ensure the process of organizational change against the demands of the world and the environment in general, including: environmental profile, profile of a new era, the change, the confidence, the administrative process, leadership and the path to the spirituality; therefore an interpretation and application to the evolution of each organization based on their individuality and purposes have been carried out.